Turismo como estrategia para la conservación y uso sostenible de los recursos del Atacazo. - Cevallos Bayas, Camila Abigail (2023)
The main objective of the research project is to be an updated document about the current state of the paramo in the study volcanic complex Atacazo. "El Atacazo" corresponds to the south of the city of Quito-Guamaní, where tourism is proposed as an element of the conservation of the ecosystem as well as attractions and their sustainable use. It is exploratory research, with observation, potential and inductive methods used in 3 non-random groups. The study variable was based on the perspective of conservation of the paramo, its strategies, and characteristics of the community that can be used as a strength for the implementation of tourism. The population was conformed of community and neighborhood presidents, people living for more than seven years within the paramos, and people directly related to tourism and companies involved, whose point of view brought attributes cultural and natural ones, and, at the same time the perspective of the paramo conservation. The instrument used was semi-structured interviews, MINTUR files, and the beginning of the SWOT matrix to complement the first objective. Followed by Molina's hierarchical model to determine the potential, which demonstrated a vast influence to receive a flow of tourists. Finally, for the creation of strategies, the SWOT matrix was continued, getting results that were processed through the SWOT matrices allowed the correct execution and choice of alternative and dynamic strategies that the place needs, such as product diversification through tourism.